Badawi - Altrad, Mohed (Black Cat, 2016)
Follows the course of the life of a Syrian orphan boy named Maeiouf whose struggles to attain an education lead him to France and Abu Dhabi, where even his great success can't keep him from being drawn back to the life he thought forgotten.